Recreation for the physically handicapped - Pomeroy, Janet (New York : Macmillan Publishing Company, 1964)
This volume is designed to interpret the widespread need by the physical handicapped for opportunities to engage in satisfying and constructive recreation activities.
Part One. The Handicapped and Recreation -- Part Two. Organization and Operation -- Part Three. Activities and Programs.
Includes bibliographical references and index.
Keywords: DISABLED PERSON